2015
DOI: 10.1371/journal.pone.0126606
|View full text |Cite
|
Sign up to set email alerts
|

Brain and Muscle Redox Imbalance Elicited by Acute Ethylmalonic Acid Administration

Abstract: Ethylmalonic acid (EMA) accumulates in tissues and biological fluids of patients affected by short-chain acyl-CoA dehydrogenase deficiency (SCADD) and ethylmalonic encephalopathy, illnesses characterized by neurological and muscular symptoms. Considering that the mechanisms responsible for the brain and skeletal muscle damage in these diseases are poorly known, in the present work we investigated the effects of acute EMA administration on redox status parameters in cerebral cortex and skeletal muscle from 30-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…The increased lipid peroxidation observed in the head of 10-day-old flies indicated that HP IX crossed the gut and affected the head more strongly than the thorax. Similar results were reported by Schuck et al (2015) who found that ethylmalonic acid-injected rats presented a marked increase in TBARS levels in both the cerebral cortex and muscle, and the registered levels in the former tissue were higher than in the latter tissue. As indicated by Rao & Balachandran (2002), the brain is particularly vulnerable to free radical damage because membrane lipids contain high levels of polyunsaturated fatty acid side chains, and consume large quantities of oxygen.…”
Section: Figuresupporting
confidence: 90%
“…The increased lipid peroxidation observed in the head of 10-day-old flies indicated that HP IX crossed the gut and affected the head more strongly than the thorax. Similar results were reported by Schuck et al (2015) who found that ethylmalonic acid-injected rats presented a marked increase in TBARS levels in both the cerebral cortex and muscle, and the registered levels in the former tissue were higher than in the latter tissue. As indicated by Rao & Balachandran (2002), the brain is particularly vulnerable to free radical damage because membrane lipids contain high levels of polyunsaturated fatty acid side chains, and consume large quantities of oxygen.…”
Section: Figuresupporting
confidence: 90%
“…In addition, elevated succinate levels and mitochondrial dysfunctions have been associated to an increased oxidative stress, which has been extensively described in the brain of this animal model 34 , 35 , and in ADHD patients 36 – 39 . The higher brain levels of 2-ethylmalonate also observed in SHR/NCrl rats are consistent with an increased oxidative stress as it is a reliable lipid peroxidation biomarker 40 . Thus, the higher brain levels of glucuronate detected could reflect an elevated activity of the pentose phosphate pathway due to the increased oxidative stress, as the pentose phosphate pathway is used by neurons to regenerate glutathione 41 .…”
Section: Discussionsupporting
confidence: 67%
“…In human cells, silencing of ECHDC1 decreased ethylmalonyl-CoA decarboxylase activity and increased the formation of ethylmalonic acid (EMA) (11). EMA induces oxidative stress in skeletal muscle and in the cerebral cortex (18,19). Human cancer cells are more sensitive to oxidative stress, which inhibits cell proliferation (20).…”
Section: Discussionmentioning
confidence: 99%